Determinants of Increased Childbirth at Home during the Covid-19 Pandemic - Susanti Melinda; Sri Anggarini Rasyid; Sitti Marya Ulva (Universitas Mandala Waluya, 2021)
During the Covid-19 pandemic, there was an increase in deliveries of pregnant women in non-health facilities, one of which was in the Motui Health Center area, namely 77.77% of pregnant women gave birth at home. This is because pregnant women are afraid of getting Covid-19 if they give birth in health facilities and are also afraid to do a Rapid Test. This study intends to determine the relationship between compliance and knowledge with an increase in the number of deliveries at home during the Covid-19 pandemic in the working area of ​​the Motui Health Center, Ranombupulu Village, Motui District, North Konawe Regency. This research method is quantitative analytic through a Cross Sectional Study design. The population is 34 people where the sampling technique uses total sampling so that the number of samples is 34 respondents. Data analysis used chi-square test. The results showed that the ANC visit compliance variable with a value of X2count=12.255 and a value of φ=0.600, and a knowledge variable with a value of X2count=9.722 and a value of φ=0.535. The conclusion of the study is that there is a strong relationship between the ANC visit compliance and knowledge with an increase in the number of deliveries at home in Ranombupulu Village. It is recommended that pregnant women increase their understanding of childbirth at the puskesmas during the Covid-19 period, including preventive measures for Covid-19 and carry out a complete examination to prevent complications during pregnancy.